2017
DOI: 10.1016/j.ccell.2017.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitive Relapse in Small Cell Lung Cancer Proceeds through an EZH2-SLFN11 Axis

Abstract: SUMMARY Small cell lung cancer is initially highly responsive to cisplatin and etoposide but in almost every case becomes rapidly chemoresistant, leading to death within one year. We modeled acquired chemoresistance in vivo using a series of patient-derived xenografts to generate paired chemosensitive and chemoresistant cancers. Multiple chemoresistant models demonstrated suppression of SLFN11, a factor implicated in DNA damage repair deficiency. In vivo silencing of SLFN11 was associated with marked depositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
371
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 419 publications
(381 citation statements)
references
References 46 publications
8
371
2
Order By: Relevance
“…These included NFIB (74), SLFN11 (75,76), BCL2 (28), SOX2 and EZH2 (70,77). Figure 9 is a summary of the main differences between the NE high and low subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…These included NFIB (74), SLFN11 (75,76), BCL2 (28), SOX2 and EZH2 (70,77). Figure 9 is a summary of the main differences between the NE high and low subtypes.…”
Section: Discussionmentioning
confidence: 99%
“…SLFN11 is actively recruited to sites of DNA damage, inhibiting HR respectively) [54] and activating a cellular replication-stress response [55,56]. SLFN11 suppression has been associated with chemoresistance in SCLC models [57] and identified as a biomarker of PARP inhibitor response in SCLC PDX [44]. Circulating tumour cell enumeration was undertaken at baseline and after 1 cycle of chemotherapy.…”
Section: Veliparibmentioning
confidence: 99%
“…A recent clinical trial demonstrated that rovalpituzumab tesirine (Rova-T), a DLL3-targeted antibody-drug conjugate, exhibited marked antitumor activity and durability in recurrent or refractory SCLC (20). EZH2 is also highly expressed in SCLC, and its inhibition by EZH2 inhibitor enhances the effectiveness of current standard chemotherapy (21). Higher expression of DLL3 and EZH2 in SCLC was associated with a higher rate of response to Rova-T and EZH2 inhibitor, respectively; thus, DLL3 and EZH2 expression may be a candidate predictive biomarker for SCLC treatment.…”
Section: Introductionmentioning
confidence: 99%